Arabidopsis telomerase takes off by uncoupling enzyme activity from telomere length maintenance in space - Borja Barbero Barcenilla; Alexander D. Meyers; Claudia Castillo-González; Pierce Young; Ji-Hee Min; Jiarui Song; Chinmay Phadke; Eric Land; Emma Canaday; Imara Y. Perera; Susan M. Bailey; Roberto Aquilano; et al. (Nature Communications, 2023)
Abstract Spaceflight-induced changes in astronaut telomeres have garnered significant attention in recent years. While plants represent an essential component of future long-duration space travel, the impacts of spaceflight on plant telomeres and telomerase have not been examined. Here we report on the telomere dynamics of Arabidopsis thaliana grown aboard the International Space Station. We observe no changes in telomere length in space-flown Arabidopsis seedlings, despite a dramatic increase in telomerase activity (up to 150-fold in roots), as well as elevated genome oxidation. Ground-based follow up studies provide further evidence that telomerase is induced by different environmental stressors, but its activity is uncoupled from telomere length. Supporting this conclusion, genetically engineered super-telomerase lines with enhanced telomerase activity maintain wildtype telomere length. Finally, genome oxidation is inversely correlated with telomerase activity levels. We propose a redox protective capacity for Arabidopsis telomerase that may promote survivability in harsh environments.